Organic bee pollen: botanical origin, nutritional value, bioactive compounds, antioxidant activity and microbiological quality - Feás, Xesús (2014)
Organic bee pollen (BP, n = 22) harvested from the Douro International Natural Park (DINP, Portugal) was studied. Nine botanical families were found in the mixture of the samples. The water activity and pH ranged 0.21–0.37 and 4.3–5.2, respectively. The BP analyses averaged 67.7% carbohydrates, 21.8% crude protein, 5.2% crude fat and 2.9% ash. The energy ranged from 396.4 to 411.1 kcal/100 g. The principal fatty acid found was linolenic, followed by linoleic acid, palmitic acid and oleic acid. The phenolic and flavonoid contents varied from 12.9 to 19.8 mg of gallic acid equivalents/g of extract and from 4.5 to 7.1 mg of catechin equivalents/g of extract, respectively. The scavenger activity and β-carotene bleaching assays values (EC50) were 3.0 ± 0.7 mg/mL and 4.6 mg/mL ± 0.9 mg/mL, respectively. E. coli, sulphite-reducing Clostridia, Salmonella and S. aureus were not found. Since there are studies indicating appreciable differences among BPs from different regions, the full characterization of BP from diverse origins still appears to be a sound research priority in order to obtain reliable data about this beehive product.